2020
DOI: 10.11606/s1518-8787.2020054002078
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with active transportation to school for adolescents

Abstract: OBJECTIVE: To verify the prevalence and factors associated with active transportation to school (ATS) among Brazilian adolescents attending public schools. METHODS: Crossectional study with a representative sample of 1,984 adolescents (55.9% girls). Sociodemographic variables included were: gender, age, parental schooling, and socioeconomic status. Psychosocial factors included were: social support from parents and friends for physical activity. Walking, cycling, or skateboarding to school were considered mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The results show a 36.5% prevalence of AC to school. These results are similar to the 37.5% of Brazilian adolescents [ 43 ] but lower than the 54.3% of the Chinese adolescents [ 18 ]. At the national level, these results are in line with those of previous Portuguese HBSC studies (e.g., 35% in Loureiro et al [ 44 ]).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results show a 36.5% prevalence of AC to school. These results are similar to the 37.5% of Brazilian adolescents [ 43 ] but lower than the 54.3% of the Chinese adolescents [ 18 ]. At the national level, these results are in line with those of previous Portuguese HBSC studies (e.g., 35% in Loureiro et al [ 44 ]).…”
Section: Discussionsupporting
confidence: 81%
“…Regarding age, we identified that AC has a higher probability to be performed more often by older adolescents. Age is an important moderator for adolescent AC since older adolescents may have fewer personal safety concerns due to greater autonomy and less dependence on parents [ 46 ], especially in the case of girls [ 43 ]. Furthermore, they have less parental control, which significantly contributes to the adolescents’ decisions about AC [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also associated with a better cardiometabolic health profile [ 10 ]. There are also other aspects that are increasingly important in modern society, such as economic and social issues and the ecological co-benefits [ 11 , 12 ]. From an educational perspective, AT stimulated at an early age [ 13 ] can help consolidate this behavior throughout life [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of active transportation contributes decisively to compliance with PA recommendations in adolescents, both in intensity and frequency (Kek et al, 2019). In this sense, the performance of PA shared with parents and greater social support of this activity, are key factors capable of predicting the frequency of active transportation by adolescents (Camargo et al, 2020). Similarly, greater enjoyment of PA also seems to contribute significantly to the likelihood of making active trips to school (Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%